EMPOWERMENT OF VILLAGE COMMUNITIES THROUGH INTEGRATED ECOFARMING PROGRAMS (Case Study in Asinan Village, Bawen District, Semarang Regency) - Farikhah, Siti; Fatimah, Nurul; Luthfi, Asma (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol.12, No.1, 2018DO - 10.24843/SOCA.2018.v12.i01.p01, 2018)
The vast potential of agricultural land in Asinan Village, which has been processed using chemical fertilizers, has received attention from Bank Indonesia in the Central Java region to become a Development Village. Through this assisted village, Bank Indonesia provides an agricultural community empowerment program that is integrated with livestock known as integrated ecofarming. This study uses a qualitative method. The results showed that (1) Implementation of the integrated ecofarming program in Desa Asinan can be said that the program failed because it was unsustainable, (2) Obstacles in the integrated ecofarming program include land use and management patterns of farmers using the maro system and rental systems, irrigation systems which still depends on nature, lack of supply of organic fertilizers, habits and mindsets of farmers who are not easily changed because they are accustomed to using chemical fertilizers, facilities and infrastructure that are not maximized, product marketing is difficult because rice has not been certified organic, (3) Community participation seen from participation decision making, participation in implementation, benefit taking, participation in evaluations and in Longwe's analysis the participation of the Asinan Village community is included in the welfare criteria.